2017
DOI: 10.1177/1940082917698467
|View full text |Cite
|
Sign up to set email alerts
|

Wetland, Forest, and Open Paddy Land Are the Key Foraging Habitats for Germain’s Swiftlet (Aerodramus inexpectatus germani) in Southern Thailand

Abstract: Germain's swiftlets (Aerodramus inexpectatus germani) are farmed regularly in Southeast Asia and produce highly valuable nests for which there is an increasing demand. Some populations of this species are thought to be decreasing, but little is known about the habitat used by swiftlets for foraging. Here, we focused on this swiftlet's foraging habitat selection and describe their daily and seasonal variations in habitat use. We predict that the prey capture attempts would be highest during twilight periods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Land cover in Kota Bangun District, which consists mainly of shrubs and forests, also supports the availability of flying insects as swiftlet feeds. In Thailand, wetland, forest and open paddy lands are the main sources of feed supply for swiftlets (Petkliang et al 2017).…”
Section: Business Model 1 (512 M 2 Swiftlet House)mentioning
confidence: 99%
See 1 more Smart Citation
“…Land cover in Kota Bangun District, which consists mainly of shrubs and forests, also supports the availability of flying insects as swiftlet feeds. In Thailand, wetland, forest and open paddy lands are the main sources of feed supply for swiftlets (Petkliang et al 2017).…”
Section: Business Model 1 (512 M 2 Swiftlet House)mentioning
confidence: 99%
“…The preferred habitats for swiftlets are open waters, forests, and rice fields. In these habitats, many flying insects can be found by the swiftlets as the food sources (Petkliang et al 2017;Ahmad et al 2019). In case that swiftlets are farmed, the availability of abundant food sources affects the swiftlets entering the swiftlet houses built by farmers (Ibrahim et al 2009;Idris et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that a forest extent of 2,000-6,000 meters from buildings improved EBN production efficiency. This increase of efficiency due to forest extent may be attributed to the fact that forests provide nest material and food for swiftlets (Petkliang et al, 2017;Quang et al, 2002;Tylianakis et al, 2005). The swiftlets nesting in areas near forests can catch larger amounts of food, such as Homoptera, than those in urban and rural areas (Lourie & Tompkins, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our estimation results reported in Table 2 indicate that forest extent and the existence of ponds around buildings improve EBN production efficiency. This efficiency increase might be attributed to the fact that natural resources, including forests and ponds, provide nest material and food for the swiftlets (Quang et al, 2002;Tylianakis et al, 2005;Petkliang et al, 2017). The swiftlets nesting in areas near forests, such as the Homoptera, can catch a larger amount of food compared to urban and rural areas (Lourie and Tompkins, 2008).…”
Section: Discussionmentioning
confidence: 99%